Kajian Penyediaan Ruang Terbuka Hijau dalam Mewujudkan Kota Ramah Lingkungan di Kecamatan Gedebage Kota Bandung - Dynanti; Yulia Asyiawati; Wishaguna (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. This study aims to examine the provision of green open space in the Gedebage District area to create an environmentally friendly city based on the aesthetic aspect of its function as an enhancer of the beauty of the environment and urban landscape. The background of this research is the unavailability of fulfilling 20% of Public Green Open Spaces in Gedebage District so that a study is needed regarding the provision of Green Open Spaces based on aesthetic functions to address urban problems in the aesthetic aspect. The research method used is descriptive descriptive with a green city approach, especially green open space indicators. Data collection was carried out through questionnaires, field observations and literature studies. The analytical method used is scenic beauty estimation analysis (SBE) and analysis of perceptions and preferences to determine the value of the aesthetic quality of green open spaces in Gedebage District, which will then be used as a reference for the provision of green open spaces based on aesthetic functions in the future. The output or results of the research will produce recommendations for types of facilities based on the Green Open Space typology that are adjusted to applicable standards and in accordance with the characteristics of the research study area. Abstrak. Penelitian ini bertujuan untuk mengkaji penyediaan ruang terbuka hijau pada wilayah Kecamatan Gedebage untuk mewujudkan kota yang ramah lingkungan berdasarkan kepada aspek fungsi estetika sebagai peningkat keindahan lingkungan dan lansekap kota. Latar belakang penelitian ini adalah belum tersedianya pemenuhan 20% Ruang Terbuka Hijau Publik di Kecamatan Gedebage sehingga diperlukan kajian mengenai penyediaan Ruang Terbuka Hijau berdasarkan fungsi estetika guna mengatasi permasalah perkotaan pada aspek estetika. Metode penelitian yang digunakan adalah kuantitatif deskriptif dengan pendekatan kota hijau khususnya indikator green open space. Pengumpulan data dilakukan melalui kuesioner, observasi lapangan dan studi literatur. Metode analisis yang dilakukan yaitu analisis scenic beauty estimation (SBE) dan analisis persepsi dan preferensi untuk mengetahui nilai kualitas estetika ruang terbuka hijau di Kecamatan Gedebage yang selanjutnya penilaian tersebut akan dijadikan acuan untuk peyediaan ruang terbuka hijau berdasarkan fungsi estetika di masa yang akan datang. Output atau hasil penelitian akan menghasilkan rekomendasi jenis fasilitas berdasarkan tipologi Ruang Terbuka Hijau yang disesuaikan dengan standar yang berlaku dan sesuai dengan karakteristik wilayah studi penelitian.